Truth or dare [videorecording (DVD)] - Wadlow, Jeff; Hale, Lucy, 1989-; Posey, Tyler, 1991-; Beane, Violett, 1996- (Universal Pictures Home Entertainment, 2018)
A harmless game of truth or dare among friends turns deadly when someone, or something, begins to punish those who tell a lie or refuse the dare.